Creative Individuality as a Subject of Creative Pedagogy - Roskvas, Ihor (Pedagogical Discourse, 2016)
The article deals with the theory and practice of development of creative individuality of the future skilled worker in the process of creative professionally-pedagogical training. Formation of creative individuality is explained by the significant changes that occur in the modern Ukrainian education. It is stated in the article that according to the world standards the modern skilled worker is an artistic and creative personality, who has the original problem-production and critical thinking, the creator of multivariate programs, referring to progressive international experience and modern technologies and interprets them in certain operating conditions based on the diagnostic goal setting and reflex. The article considers the phenomenon of «professional reflection» as an integral personality trait that significantly affects the formation of creative individuality of the student. The author analyzes the different approaches to the problem of creativity and peculiarities of application of creative approach to professional-pedagogical training of the future skilled workers. The qualities, which significantly affect the efficiency of construction of professional creative data, have been studied. The basis on which the cognitive demand has been determined, and on which the creative personality of the future skilled worker develops. The concept of formation and development of creative thinking of students has been offered, while the learning is considered as a process of solving professionally oriented mental tasks, according to which envisages the introduction of forms and methods of active learning of students, development of their cognitive independence in teaching-scientific-research activities. The fundamental mechanisms of development of individuality taking into account many factors, have been analyzed. General meaning of the term «creative individuality» and «creativity» in philosophy and sociology has been revealed in the research. It is indicated what could be the result of creative activity, and what contains a product of creativity. The author concludes that the creative individuality of the employee and its development in creative pedagogy should be regarded as a function of the whole personality, which is conditioned by corresponding psychological-professional conditions and the high level of development of its special and personal features. Key words: training of future skilled worker, creative approach, specialized schools, and creative thinking skills, creative personality, intellectual activity, and professional reflection.